Optimal Design of Negative Stiffness Devices for Highway Bridges Using Performance-Based Genetic Algorithm - Tong, Sun; Tianqi, Zhu; Li, Sun; Hao, Zhang (Frontiers in Physics, 2021)
Parameter optimization analysis on the negative stiffness device (NSD) installed in benchmark highway bridge is carried out in this study. Optimization parameters and constrain conditions are determined in accordance with the characteristics of NSD, and an object function is designed with safety and comfort being considered. Individual fitness value related cross and mutation operators are designed to protect excellent chromosome and improve the efficiency and convergence of computation. Then, the genetic algorithm is used to realize parameter optimization of the NSD used in a benchmark highway bridge. Dynamic responses of structures without devices, with devices possessing random and optimal parameters are compared. By analyzing the time-history curves of displacement and acceleration, it can be concluded that dynamic responses of the structure decrease obviously when the NSD is added, and a better seismic reduction effect can be reached when the NSD is designed optimally in accordance with the optimization method, and different earthquake excitations have slight influence on the optimization results.